University Preferences and Careers with the highest demand in the San Martín Region 2017 -2019 - Paz Vilchez, José Eber (2017)
The present research was developed in the department of San Martin. The main objective of this study is to know the preferences demanded by the students at the time of choosing a university career, as well as the preference of the University for their higher education studies. The method of study was descriptive, cross-sectional design. The study population consisted of 1435 students from 14 to 20 years to come coursing in 3rd year to the 5th of secondary which took as a reference the Provinces and Districts of the Region San Martin. Tarapoto, Rioja, Moyobamba, New Cajamarca, Juanjuí, Yurimaguas, Bellavista Lamas and Tocache. The instrument was administered that was used to measure the preferences of the races more demanding. By which were performed different questions, based the choice of a career and educational center where to study. The result is obtained located in the first place to the National University of San Martin with a 25.6%, (368), followed by the Universidad Peruana Union with a 18.8% (270), taking such as racing flags medicine with 15.7% (225), followed by civil engineering 14.4% (217) and Business Administration 11.2% (161). It is concluded that in the region of San Martin demand exists for universities and traditional careers.